Computational Evaluation of Antibacterial Activity of Acalypha indica L. Phytochemicals Against Staphylococcus aureus DNA Gyrase - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
This study investigated the antibacterial potential of phytochemical compounds derived from Acalypha indica L. against the DNA gyrase of Staphylococcus aureus using an in silico computational approach. Phytochemical structures were collected from established compound databases and subjected to geometry optimization to ensure conformational stability before molecular docking analysis. Docking simulations were carried out using AutoDock Vina to evaluate the binding affinity and interaction profiles of each ligand with the ATP-binding domain of DNA gyrase, a critical enzyme involved in bacterial DNA replication. The three-dimensional structure of S. aureus DNA gyrase was obtained from the Protein Data Bank and prepared through removal of water molecules, addition of polar hydrogens, and refinement of active-site residues. Among the screened ligands, five compounds exhibited strong predicted affinities, with binding energies ranging from -6.8 to -9.1 kcal/mol. Compound C demonstrated the most favorable interaction, forming stable hydrogen bonds and extensive hydrophobic contacts within the catalytic pocket, suggesting a strong inhibitory potential. Compound E also showed a high affinity, although its orientation within the binding site was slightly less optimal. ADMET predictions indicated that all top candidates satisfied drug-likeness criteria, showed good absorption potential, and presented low toxicity risks. Overall, the findings highlight that Acalypha indica L. contains bioactive constituents with promising inhibitory activity against bacterial DNA gyrase. These results support the traditional use of the plant in antimicrobial applications and provide a foundation for further experimental validation through in vitro enzyme inhibition assays and in vivo studies to confirm their therapeutic relevance.